Presidential influence on parliamentary election timing and the electoral fate of prime ministers. Issue 2 (3rd April 2018) - Morgan-Jones, Edward; Schleiter, Petra
ABSTRACT: Most presidential heads of state in parliamentary and semi-presidential democracies have constitutional powers to influence early election calling, which enable them to influence the conditions under which prime ministers are held accountable by the electorate. We examine whether presidents use theses powers to shape the timing of early elections for partisan advantage and to influence the electoral performance of prime ministers. Drawing on data from 193 elections in 18 European democracies (1945–2013), we find that presidents with significant dissolution powers enable incumbents in governments that include the president's party to realise a significant electoral bonus compared with governments that exclude the party of the president.